Metric handbook : planning and design data. - Littlefield, David, ....- (Oxford : Architectural Press, 2008)
Originally devised as a guide for converting from imperial to metric measurements, 'The Metric Handbook' has since been totally transformed into a handbook of planning and design data for construction professionals. This new edition has been updated to account of the most recent changes to regulation and practice, in particular the increasing emphasis on environmental legislation - to meet the needs of the modern building design professional. The Metric Handbook deals with all the principal building types from airports, factories and warehouses, offices shops and hospitals, to schools, religious buildings and libraries. For each type the book gives the basic design requirements and all the principal dimensional data, as well as succinct guidance on how to use the information and what regulations the designer may need to be aware of. As well as buildings the Metric Handbook deals with broader aspects of design such as materials, acoustics and lighting, and general design data on human dimensions
and space requirements. Contents include: - Notation - Basic Design Data - Design and Construction Practice and Techniques - Re-use/Refurbishment/Whole Life Costs - Design Basics: Buildings & Movement - Design Basics: Spaces/Urban Design - Houses and Flats - Student housing - Homes for the elderly - Hotels - Offices - Retail Trading - Factories and Workshops - Industrial Storage - Agricultural Buildings - Eating and Drinking - Sports Facilities: Indoor - Sports Facilities: Outdoor - Leisure and Community Facilities - Schools and Nurseries - Higher Education - Laboratories - Primary Health Care - Hospitals - Payment offices - Public Buildings - Museums and Art Galleries/Visitor Centres - Libraries and Information Centres / Archives - Terminals and Transport Interchanges - Parking - Sound and Vision Studios - Auditoria - Places of Worship - Structure - Materials - Doors/Windows/Stairs - Heating and Ventilation - Light; Sound; Fire; Security - Designing for the Disabled - Access for Maintenance - Service
Distribution